2019
DOI: 10.1186/s12886-019-1233-8
|View full text |Cite
|
Sign up to set email alerts
|

Purtscher-like retinopathy presented a honeycomb-like pattern in optical coherence topography angiography

Abstract: Background: To report a case of Purtscher-like retinopathy (PUR) and the optical coherence tomography (OCT) and OCT angiography (OCT-A) findings before and after treatment. Case presentation: A 65-year-old male presented with acute onset of vision loss for 2 weeks. Fundus examination revealed cotton-wool spots, retinal haemorrhage, and Purtscher flecken spread around the optic disc in the right eye. He was diagnosed with Purtscher-like retinopathy because he lacked any traumatic medical history. OCT presented … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 9 publications
5
7
0
Order By: Relevance
“…2,[6][7][8] There are few case reports of Purtscher-like retinopathy accompanied by OCT-A images, but, to our knowledge, none in association with retrobulbar anesthesia. 4,9,10 Similar to the imaging in the study by Li et al, our OCT-A showed poor perfusion of the inner retinal vascular plexuses and a honeycomb-like hypointensity in outer retina/choriocapillaris layers. 4 These ischemic areas corresponded to the Purtscher flecken noted in the inner retina.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…2,[6][7][8] There are few case reports of Purtscher-like retinopathy accompanied by OCT-A images, but, to our knowledge, none in association with retrobulbar anesthesia. 4,9,10 Similar to the imaging in the study by Li et al, our OCT-A showed poor perfusion of the inner retinal vascular plexuses and a honeycomb-like hypointensity in outer retina/choriocapillaris layers. 4 These ischemic areas corresponded to the Purtscher flecken noted in the inner retina.…”
Section: Discussionsupporting
confidence: 87%
“…4,9,10 Similar to the imaging in the study by Li et al, our OCT-A showed poor perfusion of the inner retinal vascular plexuses and a honeycomb-like hypointensity in outer retina/choriocapillaris layers. 4 These ischemic areas corresponded to the Purtscher flecken noted in the inner retina. Li et al conjectured that this choroidal lobular infarction was the causative pathogenesis for lack of visual recovery in their patient.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Histopathology and electroretinography results and late changes at the RPE level visualized upon SD-OCT and described in the literature provide further evidence of choroidal involvement in PUR/PRL [ 6 ]. Other studies have suggested that a honeycomb-like hypointense signal from the choriocapillaris layer on OCT-A indicates the involvement of the choroid with ischemia [ 24 ]. A hypointense signal pattern in the choriocapillaris layer observed on OCT-A was also found with our patient, most likely as an artifact projection from the retinal layers.…”
Section: Discussionmentioning
confidence: 99%